Winter Counts - Weiden, David Heska Wanbli, 1963- (New York, NY : Ecco, an imprint of HarperCollinsPublishers, 2020)
Virgil Wounded Horse is the local enforcer on the Rosebud Indian Reservation in South Dakota. When justice is denied by the American legal system or the tribal council, Virgil is hired to deliver his own punishment, the kind thats hard to forget. But when heroin makes its way into the reservation and finds Virgils nephew, his vigilantism suddenly becomes personal. He enlists the help of his ex- girlfriend and sets out to learn where the drugs are coming from, and how to make them stop. They follow a lead to Denver and find that drug cartels are rapidly expanding and forming new and terrifying alliances. And back on the reservation, a new tribal council initiative raises uncomfortable questions about money and power. As Virgil starts to link the pieces together, he must face his own demons and reclaim his Native identity. He realizes that being a Native American in the twenty-first century comes at an incredible cost
Keywords: Indians of North America -- Fiction; Lakota Indians -- Fiction; Lakota Indians -- Drug use; Fiction; Heroin industry -- Fiction; Drug traffic -- Fiction; Vigilantes -- Fiction; Rosebud Indian Reservation (S.D.) -- Fiction; Fiction; Mystery fiction; Thrillers (Fiction); Detective and mystery fiction